Do Western Methods Work in South-East Asia? A Thought From the Cross-Cultural Usability Testing of a Food Processor in Indonesia and the Netherlands - Daams, Brechtje; Hariandja, Johanna (Faculty of Psychology, Universitas Surabaya, 2005)
Currently, many European companies sell their products all over the world, not only in Europe or America but also expanding to Asia. It is therefore interesting to investigate how people from a European and an Asian culture use and perceive a product. This is done by executing across-cultural usability test in Indonesia (a South-East Asian country) and The Netherlands (a Western European country). Usability testing is not very common among people in Indonesia, and therefore not known to the public. So far, no literature can be found about usability testing in Indonesia. On the other hand, usability testing is well known and has been applied successfully in the Netherlands over the last years. Doing usability testing in Indonesia has brought some interesting findings concerning the methods used. It is shown that generally used usability research methods such as the 'think-aloud' method combined with user observation are problematic in Indonesia. It is clear that this usability testing method is not suitable for Indonesians because they do not feel comfortable with it. In this paper, we recommend that if usability testing be executed with Indonesian participants, a method should be worked out which makes them more eager to participate and feel more comfortable when participating. The acceptability and applicability of a research method should be taken into account when testing products with participants from a different culture. Dewasa ini, banyak perusahaan Eropa menjual produknya ke seluruh dunia, bukan hanya di Eropa atau Amerika, tetapi juga merambah ke Asia. Cukup menarik untuk meneliti bagaimana masyarakat dengan budaya Eropa dan Asia menggunakan dan merasakan suatu produk. Hal ini dilakukan dengan melakukan uji-gunalintas budaya di Indonesia dan di Belanda. Uji-guna belum banyak dikenal orang Indonesia, karenanya tak diketahui masyarakat pada umumnya. Sejauh ini belum ditemukan kepustakaan tentang uji-guna di Indonesia. Dilain pihak, uji-guna sudah sangat dikenal dan telah diaplikasikan dengan berhasil di Belanda akhir-akhir ini. Melaksanakan uji-guna di Indonesia menghasilkan temuan-temuan yang menarik menyangkut metode yang dipakai. Ditunjukkan bahwa metode penelitian uji-guna yang biasa dipakai seperti metode